2018
DOI: 10.22481/praxis.v14i30.4364
|View full text |Cite
|
Sign up to set email alerts
|

Expressões Da “Docência Compartilhada” Na Formação Inicial De Professores

Abstract: Este texto objetiva problematizar a Docência Compartilhada enquanto estratégiametodológica/formativa, no interior da prática pedagógica, a partir dos significados atribuídos pelasacadêmicas do curso de Pedagogia à esta experiência. Deste modo, realizamos a coleta dasinformações a partir dos relatos em reuniões com acadêmicas que participam do ProgramaInstitucional de Bolsas de Iniciação à Docência (PIBID) e dos registros coletivos construídos no“google drive” de março a junho de 2017. Para a análise dos result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…The necessary mathematical competencies of a teacher can be assessed using the CID (BREDA; FONT; PINO-FAN, 2018;BREDA et al, 2018;FONT;BREDA;SALA, 2015;FONT et al, 2018). In this paper, we try to analyze what happens with the following components of this construct: connections, autonomy, social-professional practicality, errors, representativeness of complexity, and educational innovation, which according to a previous study (GARCÍA MARIMÓN et al, 2021) seem not to be used, or are little used by teachers in their teaching plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The necessary mathematical competencies of a teacher can be assessed using the CID (BREDA; FONT; PINO-FAN, 2018;BREDA et al, 2018;FONT;BREDA;SALA, 2015;FONT et al, 2018). In this paper, we try to analyze what happens with the following components of this construct: connections, autonomy, social-professional practicality, errors, representativeness of complexity, and educational innovation, which according to a previous study (GARCÍA MARIMÓN et al, 2021) seem not to be used, or are little used by teachers in their teaching plans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is based on the premise that educators have to be able to reflect critically (and in a certain way also systematically) on their own educational praxis. For this, it is suggested that they take as a theoretical reference point the Didactic Mathematical Knowledge and Competences Model (DMKC) of the teacher, proposed by the OSA (GODINO; BATANERO; FONT, 2007FONT, , 2019GODINO et al, 2016;GODINO et al 2017;FONT;BREDA;SALA, 2015;BREDA;SILVA;DE CARVALHO, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Las competencias matemáticas necesarias de un maestro pueden ser valoradas utilizando los CID (BREDA; FONT; PINO-FAN, 2018;BREDA et al, 2018;FONT;BREDA;SALA, 2015;FONT et al, 2018). En este trabajo intentamos analizar qué sucede con los siguientes componentes de este constructo: conexiones, autonomía, utilidad socio laboral, errores, representatividad e innovación educativa, que de acuerdo con un estudio previo (GARCÍA MARIMÓN et al, 2021) parecen no ser utilizados, o son poco usados por los maestros en sus planificaciones docentes.…”
Section: Discussionunclassified
“…Por lo tanto, se parte de la premisa que los educadores tienen que ser capaces de reflexionar de manera crítica (y en cierta manera también sistemática) sobre su propia praxis educativa. Para ello se sugiere que tomen como punto de referencia teórico el modelo del Conocimiento Didáctico Matemático del profesor (CCDM), propuesto por el EOS (GODINO; BATANERO; FONT, 2007FONT, , 2019GODINO et al, 2016;GODINO et al, 2017;FONT;BREDA;SALA, 2015;BREDA;SILVA;DE CARVALHO, 2016).…”
Section: Introductionunclassified
“…O Enfoque Ontossemiótico do Conhecimento e Instrução Matemática (EOS) é um "modelo ontológico e semiótico da cognição, o qual proporciona critérios para identificar os estados possíveis das trajetórias epistêmica e cognitiva e o emprego da 'negociação de significados' como noção chave para a gestão das trajetórias didáticas" (Godino, Batanero & Font, 2008, p.11), cuja origem está nas pesquisas desenvolvidas pelo professor Godino (2008) com colaboração de Batanero (2008 e Font (2008Font ( , 2015; Gusmão (2006); Hummes, Font e Breda (2019); Kaiber, Lemos, Pino-Fan (2017) entre outros autores. O EOS direciona teórica e metodologicamente pesquisas com um conjunto de ferramentas articuladas em cinco sub-competências (análise de significados globais; gestão de configuração didática; análise normativa, análise ontossemiótica e análise da idoneidade didática).…”
Section: Os Critérios De Idoneidade Didática (Cid)unclassified